2012
DOI: 10.3109/02699052.2012.722252
|View full text |Cite
|
Sign up to set email alerts
|

Changes in personality after mild traumatic brain injury from primary blast vs. blunt forces

Abstract: These results suggest that blast forces alone can cause negativistic behavioural changes when evaluated with selected measures of personality. Further research on isolated blast-force mTBI should focus on these personality changes and their relationship to blast over-pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…6a ). Klhl2 in CA1 pyramidal cells may serve as a novel link between mTBI and the increased tendency for neuroticism observed in blast TBI 40 . Arhgap32 is primarily upregulated in CA subtype 2 cells in mTBI.…”
Section: Resultsmentioning
confidence: 99%
“…6a ). Klhl2 in CA1 pyramidal cells may serve as a novel link between mTBI and the increased tendency for neuroticism observed in blast TBI 40 . Arhgap32 is primarily upregulated in CA subtype 2 cells in mTBI.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that blast forces alone can cause deleterious behavioral changes when evaluated with selected measures of personality (35). Blast exposure has also been linked to self-perceived cognitive decline in soldiers with mbTBI (36).…”
Section: Discussionmentioning
confidence: 99%
“…Limitations include a modest sample size, all male subjects, no predeployment testing, 16 no direct comparison with identically assessed non-blast-related subjects with TBI, no formal assessment of combat exposure intensity, and absence of genetic data. We cannot rule out deficits in cognitive or behavioral domains not tested, 47,48 nor early cognitive impairments that resolved before follow-up evaluation. Likewise, Negative correlation with sustained vigilance, assessed using the hit rate block change measure from the Conners Continuous Performance Test, where similarly lower Z-scores indicate worse performance.…”
Section: Discussionmentioning
confidence: 99%